2023
DOI: 10.21037/tau-22-882
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes following radical nephroureterectomy for upper tract urothelial carcinoma: a literature review

Gabrielle Grob,
Devin Rogers,
Savio D. Pandolfo
et al.

Abstract: Background and Objective Radical nephroureterectomy (RNU) represents the gold standard treatment for non-metastatic upper tract urothelial cancer. We sought to provide a comprehensive review of reported oncologic outcomes of the RNU procedure and of factors that might impact these outcomes. Methods A non-systematic review of the literature was conducted by performing an electronic literature search using PubMed with “radical nephroureterectomy” and “oncologic outcomes” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The oncologic outcomes of UTUC patients undergoing nephroureterectomy are impacted by treatment-, patient-, and tumor-related factors [ 40 ]. For example, a higher preoperative NLR is associated with poorer outcomes, whereas perioperative chemotherapy was shown to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…The oncologic outcomes of UTUC patients undergoing nephroureterectomy are impacted by treatment-, patient-, and tumor-related factors [ 40 ]. For example, a higher preoperative NLR is associated with poorer outcomes, whereas perioperative chemotherapy was shown to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in some cases, the symptomatology and signs of UTUC may be atypical, and CTU may fail to identify the lesion, resulting in misdiagnosis or missed diagnosis. Currently, the gold standard treatment for non-metastatic UTUC is radical nephroureterectomy with bladder cuff excision ( 8 ). Radical nephroureterectomy can be performed via open, laparoscopic, and robotic approaches ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations from both the National Comprehensive Cancer Network (NCCN) [ 40 ] and the European Association of Urology (EAU) [ 41 ] to perform RNU with BCE, studies showed controversial results, thus increasing research focusing on this topic [ 36 , 42 ].…”
Section: Oncological Outcomesmentioning
confidence: 99%